Drawing on knowledge: Visual narrative analysis for critical environment and development research. (March 2022) - Simon, Gregory L; Wee, Bryan; Chatti, Deepti; Anderson, Emily
Counter-narratives to dominant development discourses are made possible using research methods designed to elicit marginalized voices. In this article, we propose a new analytical framework called the interpretive schema for drawings for analyzing visual narratives. The interpretive schema for drawings consists of five themes or interpretive lenses ( scale, centrality, inclusion, connections, and relationality ) that were generated from maps of fuelwood collection in rural India. We suggest that the interpretive schema reflects and animates a range of spatialities that are central to geographic studies of human–environment dynamics. Using the interpretive schema for drawings in this way enables us to emphasize emic socio-spatial perspectives, and offers a critical research avenue through which everyday realities can be represented, understood, and validated. While other image-based research approaches, critical cartographies and participatory mapping exercises may encourage the expression of alternative knowledges, our proposed interpretive schema for drawing presents a specific set of guidelines for interpreting and making sense of visual narratives through explicit socio-spatial analysis.